SC15 MCA/DOLS – simulation an alternative to classroom?. (3rd November 2019) - Williams, Emma; Toft, Lisa; Thompson, Sarah; Moss, Carole; Reynolds, Paula
Abstract : Background: The TEAMS simulation centre was approached in September 2018 to assist with MCA/DOLS training after the CQC enforced a section 29a to the hospital. With immediate effect the TEAMS simulation educators and the safeguarding team collaborated to try a different way of educating staff surrounding MCA/DOLS which hadn't been implemented before. Summary of educational programme/project: The Simulation scenarios were provided using live actor and used experiential learning with detailed debrief using specific learning outcomes. Triola et al (2006) showed that live actors were a valid comparible model to high fidelity manikins. Gillett (2008) agrees showing that live actors are equivalent to using manikins during simulation exercises but that both have limitations, advantages and disadvantages. We provided 2 hour sessions, four times during the day to capture all senior staff members (over 100) to feed information back to their teams and then' frontline' staff attended which has led on to interest for bespoke simulation for other departments. Pre and post confidence questionnaires were provided to assess whether the candidates felt more confident after the simulation with areas such as assessing capacity and managing challenging patients. It is important to know whether it had improved practice in the workplace using both Quantitative and qualitative data. Simulation evaluations showed positive qualitative data with most candidates expressing thoughts such as it was 'realistic, interactive' 'it demystified the process' 'open and relevant discussions' A Comparison with classroom based teaching and feedback using powerpoint and discussions/table top exercises showed that despite this rolling programme of face to face training staff were still unsure of processes and procedures surrounding MCA/DOLS when CQC inspectors questioned staff. It was then that MCA and DOLS simulation was introduced in September 2018 to compliment the delivery method to improve staffs confidence and knowledge. Stakeholder involvement included the safeguarding team and was piloted in September with support from the chief executive and board members with an alternative way of delivering education to staff. Discussions, conclusions and recommendations: Over a period of 8 months and 141 members of staff attending the simulation sessions the pre and post confidence questionnaires showed a 100% raise in confidence post simulation. This is an Ongoing project to see whether the simulation changes practice in the workplace and if possible remove section 29a from CQC in the future. References: 1. Gillett B., Peckler B., Sinert R., Onkst C., Nabors S., Issley S., Arquilla, B. Simulation in a disaster drill: Comparison of high-fidelity simulators versus trained actors. Academic Emergency Medicine (2008);15(11):1144–1151. doi:10.1111/j.1553-2712.2008.00198.x 2. Triola M., Feldman H., Kalet A. L., Zabar S., Kachur E. K., Gillespie C., Lipkin M. A randomized trial of teaching clinical skills using virtual and live standardized patients. Journal of General Internal Medicine (2006) 21, 424–429. doi:10.1111/j.1525- 1497.2006.00421.x